Fruitlet Thinning Reduces Biennial Bearing in Seven High-tannin Cider Apple Cultivars - David Zakalik; Michael G. Brown; Gregory M. Peck (HortScience, 2023)
Many European apple (Malus ×domestica Borkh.) cultivars used for making alcoholic cider have a highly biennial bearing habit. To determine target crop load recommendations, seven cider cultivars grown in a high-density orchard were hand-thinned to crop densities of 0, 3, 6, and 9 fruit/cm2 trunk cross-sectional area (TCSA) or left unthinned as a control for 3 consecutive years (2016–18). Treatments were imposed on the same trees for all 3 years. Greater year-to-year yield variability, as measured by the biennial bearing index (BBI), correlated negatively with cumulative yields both within and among cultivars. Greater crop density had a negative correlation with the amount of return bloom in all years, but reducing crop density had a negligible effect on return bloom in the “off” year. When trees were left unthinned in the high-crop “on” years there was little to no return bloom in the following year. Partial budget analysis found that manually reducing crop density would result in a positive net change in 3-year profitability for Dabinett, but not the other cultivars. Over 4 years, under conservative assumptions about fruit set, chemical thinning to 9 fruit/cm2 TCSA would likely result in increased cumulative profitability in all seven cultivars. Hand-thinning was projected to be less profitable than chemical thinning but would still result in increased net profitability over 4 years, for five of the seven cultivars. These findings highlight the horticultural and economic benefits of crop load management for cider apple orchards. Further, many high-tannin cider cultivars can sustain a higher crop density than what is recommended for fresh-market apple production and still have adequate return bloom and cumulative yields.